Terapi Aktivitas Kelompok terhadap Depresi pada Lansia - Ridwan Ridwan; Indra Febriani (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of group activity therapy on depression in the elderly at the Harapan Kita Elderly Social Institution in Palembang. This type of research is quasi-experimental, with the research design using a one-group pre-test post-test design. The results of the study in the control group before and after there was no significant difference because the p-value was 0.317, while in the treatment group, there was a significant difference between before and after group activity therapy because the p-value was 0.026, then tested post-control and post-treatment using the Mann test. -Whitney p-value of 0.268 means there is no difference between the two groups. In conclusion, group activity therapy can reduce depression in the elderly treated at the Harapan Kita Social Institution in Palembang. Keywords: Depression, Elderly, Group Activity Therapy